Сказки про медведей: сказки / худож. О. Крупенкова - Крупенкова О. (Читаем сами, 2014)
Экземпляры: ДО мл.аб. (2016) / Инвентарный номер: 52914 / Цена: 34.00. / Сис.шифр: Д / Авт.знак: С 42 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)